Community perceptions and acceptance of ivermectin for malaria control on Sumba Island, Indonesia - Diana Timoria; Christa Dewi; Claus Bøgh; Tri Baskoro; Wisnu Nurcahyo; Vincentius Arca Testamenti; Lorenz von Seidlein; Kevin Kobylinski; Mary Chambers (PLoS ONE, 2026)
Background Indonesia has made significant progress in malaria control, however hotspots such as Sumba Island continue to experience high rates of malaria transmission, driven by multiple Anopheles mosquito species. The Sumba Livestock Ivermectin for Malaria (SLIM) trial was conducted to assess the efficacy of ivermectin treatment in livestock as a vector control strategy. This accompanying social science study aimed to explore community perceptions of ivermectin-based malaria interventions, including ivermectin livestock treatment (ITL) and potential mass drug administration (MDA) in humans. Methods A social science study was conducted alongside the SLIM trial between November 2022 and September 2023 across four villages in Southwest Sumba. Qualitative and participatory approaches were used to explore community perceptions. 75 individuals (>18 years old) from the SLIM study village sites were included in four focus group discussions (59 individuals) and 16 individual in-depth interviews. We also held four feedback meetings for all members of each study village. Community engagement activities, such as puppet shows and interactive sessions on malaria transmission, were also implemented. Data were transcribed, coded, and thematically analysed using Nvivo software. Results A total of 75 individuals participated in qualitative data collection, and approximately 650 individuals engaged in community events. Malaria was ranked as the most pressing health concern by study participants. Initial skepticism about ivermectin treatment of livestock was mitigated through trust-building efforts such as village meetings and respectful communication. Community members actively contributed to the trial, demonstrating acceptance of ivermectin treatment of livestock and expressing interest in future research participation. While there was openness to mass drug administration for humans, concerns about safety, particularly for children, were raised. Local authority approval was deemed essential for intervention acceptance. In one village, low social cohesion posed barriers to research participation, highlighting the importance of engagement before the trial started. Conclusions Community perceptions of ivermectin-based malaria control strategies were shaped by trust, engagement, and cultural considerations. In this case there were multiple engagement activities built into the study – before, during and after the research, with stakeholders in local government and village leaders as well as with animal owners, other community members and children. The findings of this social research underscore the need for, and benefits of, sustained, respectful communication, partnership with local leaders and inclusive stakeholder engagement in malaria research. Future malaria control interventions should also account for local social dynamics, ensuring informed community participation to enhance trial feasibility and acceptance.